Impact Evaluation of Development Interventions: A Practical Guide - White, Howard; Raitzer, David (Asian Development Bank, 2017)
This book offers guidance on the principles, methods, and practice of impact evaluation. It contains material for a range of audiences, from those who may use or manage impact evaluations to applied researchers .